Analisis Sistem Ventilasi untuk Meminimalisir Terjadinya Swabakar pada Tambang Batubara Bawah Tanah THC 04 CV. Tahiti Coal, Sangkar Puyuh, Talawi, Sawahlunto - Multavich Multavich; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2021)
May 21, 2020 CV. Tahiti Coal has experienced a self-burning or also known as spontaneous combustion of coal (sponcom). The incident occurred at branch 401 B of the tunnel THC 01. Preventing the occurrence of sponcom in other mine tunnel, the research of ventilation system was carried out on the tunnel THC 04. This location was chosen because it has the potential to experience a sponcom. Research was conducted to obtain the causative factors that allow the occurrence of sponcom and continued with the design of ventilation systems to reduce the likelihood of sponcom. The results of this study show that the main factor that can conduce sponcom in the tunnel THC 04 is the lack of air quantity. The minimum quantity of air that can control heat and humidity is 8.7 m3/s, while the quantity of air in tunnel THC 04 is 3.03 m3/s. Based on measurements taken, the air temperature at THC 04 ranges from 29°C to 31°C, and humidity is between 90% to 100%. Therefore, the researchers designed the ventilation system by creating a translucent hole that leads to the surface and placing an exhaust fan at the end of the hole. This design can make the air quantity at THC 04 increase to 15.5 m3/s.